The Improving of the Quality Resources of Gedog Batik Craftsmen in Tuban Regency - Muslichah Erma Widiana; Nova Retnowati; Agus Slamet; Tri Sagirani (Indonesian Journal of Cultural and Community Development, 2020)
This study aims to improve business management of partner business UD. Batik "Lestari Arts". The Government of Indonesia has prepared a number of policies to protect and prepare micro, small and medium-sized businesses to produce high-quality products that have high competitiveness. Tuban is one of the towns in East Java that has an MSME named UD Batik "Lestari Arts" that produces superior products in the form of gedog batik. The Regional Superior Product Development Program, partnering with UD. Batik "Lestari Arts", resulted in improvements on two main focuses of partner business management, namely on business resources and the use of science and technology in running a business. This program is ongoing and continuing through the activities of mentoring, monitoring and evaluating results after two years of partnership.